Connecting Pathological Cellular Mechanisms to Large-Scale Seizure Structures. Issue 8 (August 2020) - Nguyen, Quynh-Anh; Moolchand, Prannath; Soltesz, Ivan
Abstract : Epilepsy is a neurological disorder characterized by recurrent seizures, where abnormal electrical activity begins in a local brain area and propagates before terminating. In a recent study, Liou and colleagues used multiscale computational modeling to gain mechanistic insights into clinical seizure dynamics based on cellular-level biophysical properties.